Multiphase analysis of hydrochars obtained by anaerobic digestion of municipal solid waste organic fraction. (September 2021) - Magdziarz, Aneta; Mlonka-Mędrala, Agata; Sieradzka, Małgorzata; Aragon-Briceño, Christian; Pożarlik, Artur; Bramer, Eddy A.; Brem, Gerrit; Niedzwiecki, Łukasz; Pawlak-Kruczek, Halina
Abstract: Digestate is a nutrient-rich substance produced by anaerobic digestion that contains organic, inorganic, and biological matter. The European Nitrates Directive (91/676/EEC) provides regulations regarding the wider implementation of the digestate. Owing to a significant amount of organic matter in the digestate, it can be utilised as a solid biofuel, soil amendment substance, or substrate for activated carbon production. However, the solid by-products of the anaerobic digestion of the municipal solid waste wet fraction cannot be used for such applications because it is still considered a waste. Hydrothermal carbonisation (HTC) was investigated as a pre-treatment method for the digestate obtained by anaerobic digestion of the municipal solid waste wet fraction. HTC was carried out at temperatures of 180, 200 and 230 °C and residence times of 30, 60 and 120 min. The value of pressure was determined based on water temperature and partial pressure of the gaseous by-products. The HTC process resulted in changes in the physical and chemical properties of the hydrochars compared to those of the raw materials. A temperature of 200 °C and residence time of 60 min during HTC were optimal for energy consumption; this hydrochar exhibited the best combustion parameters and physical properties (specific surface area). Highlights: Hydrothermal carbonisation of digestate to afford hydrochar was investigated. Effects of residence time and temperature on hydrochar were studied. Hydrochar obtained at 200 °C and 60 min characterised high energy potential. The processes showed benefits arising from the conversion of wastes into fuel. Hydrochars exhibited enhanced specific surface areas.